Predicting Olympic Medal Trends for Southeast Asian Countries Using the Facebook Prophet Model - Qohar, Bagus Al; Tanga , Yulizchia Malica Pinkan; Utami, Putri; Ningsih, Maylinna Rahayu; Muslim, Much Aziz (UIN Sunan Kalijaga Yogyakarta, 2025)
The Olympics are a world-class sporting event held every four years, serving as a meeting place for all athletes worldwide. The Olympics are held alternately in different countries. The Olympics were first held in Athens in 1896 and have now reached the 33rd Olympics, which will be held in Paris in 2024. Significant work has been conducted to develop prediction models, with a primary focus on enhancing the accuracy of predicting Olympic outcomes. However, low-performance regression algorithms are the main problem with prediction. By integrating custom seasonality with the Facebook Prophet prediction model, this study aims to enhance the accuracy of Olympic predictions. The proposed new model involves several steps, including preparing the data and initializing and fitting the Facebook-Prophet model with several parameters such as seasonal mode, annual seasonality, and prior scale. The model is tested using the Olympic dataset (1994–2024). The evaluation results indicate that this prediction model provides a reliable estimate of the total medals earned. On the Olympic Games (1994-2024) dataset, the model exhibits a very low error, as indicated by its MAE, MSE, and RMSE, and achieves an R² score of 0.99, which is close to perfect. This research shows that the model is effective in improving prediction accuracy.